EFFICACY OF BIO-PESTICIDES AGAINST SCLEROTIUM ROLFSII SACC. CAUSING COLLAR ROT OF CHICKPEA (CICER ARIETINUM L.) - JABBAR SAB; A. NAGARAJA; NAGAMMA, GOWDRA (The Bioscan, 2014)
In this study the bio efficacy of ten botanicals and eight antagonists was tested through poison food technique and dual culture technique respectively against S. rolfsii causing collar rot of chickpea. Among the 10 botanicals tested, cent per cent mycelial inhibition was observed in aqueous extract of Agave at different concentrations, followed by Henna leaves with 34.4, 71.3 and 90% at 5, 10 and 15 per cent concentration respectively and least mycelial inhibition was observed in Tridax leaves extract (5.5%) and Pongamia (7.1%). Among the eight bioagents tested against S. rolfsii, Trichoderma harzianum-55 IIHR recorded maximum inhibition of 70% followed by T. harzianum NBAII with 63% and least mycelial inhibition was observed in Pseudomonas fluorescens and Bacillus subtilis. Chickpea is one of important pulse crop which is infected with collar rot botanicals and bioagents can be used in IDM practice for management of this disease.